Association between Effect Ofsome Pro-inflammatory and Anti-inflammatory Cytokines before and After Surgical Patients (Medico Legal Update, 2021)
The aims of our study were to investigate association of some effect of pro- inflammatory and antiinflammatory cytokines before and after surgical patients through study serum concentration of, TNF-?,IL-2, IL-4, IL-6, IL-10. 35 blood samples were collected from surgical patients (17 male, 18 female)withgeneral anesthesia from Al-Diwaniyah Hospital, Iraq. Samples were taken before surgery (Tpre), the firstday) T1), third day) T3 (and fifth day (T5) after operative after skin incision.Pro-inflammatory cytokines(IL-2, IL-6, and TNF-?) and anti-inflammatory cytokines (IL-4, IL-10) were quantitatively analyzed byELISA technique.Our resultsshowed there were no significant difference (p